Determinants of Participation in Different Livelihood Diversification Strategies Among Rural Households in Western Bhutan - Wangmo, Sonam; Dorji, Ugyen; Dorji, Nedup (CV. Literasi Indonesia, 2024)
Strategies for diversifying one's source of income are crucial for the development of rural households' rain-fed agricultural economies in developing nations like Bhutan. Participating in off-farm and non-farm activities supports households in tackling a variety of difficulties, such as drought. Nonetheless, little study has been done on determining the factors that affect households’ decisions about livelihood choices in the Bhutanese context. Therefore, this study aims to examine the factors influencing rural households’ decisions to diversify their livelihood diversification strategies in western Bhutan. A multi-stage stratified random sampling method was employed to select 384 rural household heads as the study area's sample. Primary data were collected using structured questionnaires from sampled households. The factors affecting rural household heads' decision to select livelihood strategies were determined using a multivariate Probit Regression Model. The model's result showed that, while on-farm livelihood strategy was negatively and significantly correlated with distance to market, it had a strong correlation with male-headed households and land holdings. The non-farm livelihood strategy was demonstrated to be significantly and positively affected by the total income, education level, and dependency ratio; whereas, the gender of the household head had a negative and significant impact. Landholding had a negative and significant impact on off-farm livelihood strategy, while the gender of the household head had a positive and significant effect. Therefore, the study recommends policies and initiatives aimed at enhancing rural livelihood should prioritize expanding rural infrastructures, enhance smallholder households’ sustainable livelihood ability, and help to participate in income-generating activities in different ways.